2011
DOI: 10.1002/bip.21454
|View full text |Cite
|
Sign up to set email alerts
|

Influence of N‐terminus modifications on the biological activity, membrane interaction, and secondary structure of the antimicrobial peptide hylin‐a1

Abstract: Recently the peptide Hy-a1 (IFGAILPLALGALKNLIK), with antimicrobial activity, was isolated from the skin secretion of the frog Hypsiboas albopunctatus. The aim of the present work was to evaluate four analogues with introduction of acetyl group, Asp or Lys at the N-terminus of antimicrobial peptide Hy-al to supply information about the relationship of structure-biological activity. The antimicrobial activities were assayed by measuring growth inhibition of four species of bacteria and four species of fungus. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 82 publications
3
66
1
7
Order By: Relevance
“…3E, G, H) were in agreement with them being in a disordered state, with the Trp residues exposed to the solvent, producing a maximum fluorescence emission (λ max ) centered at 355 nm [27][28][29].…”
Section: Fluorescence Spectroscopymentioning
confidence: 53%
“…3E, G, H) were in agreement with them being in a disordered state, with the Trp residues exposed to the solvent, producing a maximum fluorescence emission (λ max ) centered at 355 nm [27][28][29].…”
Section: Fluorescence Spectroscopymentioning
confidence: 53%
“…15 Additionally, simple terminal modifications including N-terminal acetylation, C-terminal amidation, end-tagging and single amino acid substitutions have also been employed to alter the properties of AMPs and ACPs, with some of these peptide variants showing enhanced antibacterial and anticancer activity and cell selectivity. [16][17][18] Furthermore, previous studies have also suggested that end capping and cyclization of hexameric peptide sequences of RRWQWR and RRWWRF or end-tagging of short peptides KNK10 (KNKGKKNGKH) and GKH17…”
Section: Introductionmentioning
confidence: 99%
“…Thus, selected strategies have been performed to improve peptide stability, efficacy, delivery, and selectivity (10,21,27,32,34,38,45). As the plasma membrane is the target for cAMPs, selectivity is important and is responsible for their cytotoxicity to human cells.…”
mentioning
confidence: 99%
“…It has been determined that high helicity, hydrophobicity, and amphipathicity are correlated with an increase in eukaryotic cell toxicity (5). We have also shown that the N-terminal region is important for the hemolytic activity of synthetic peptides containing sequences from the N termini of sticholysins (7) and for selectivity of the cAMPs (10). Therefore, efforts have been undertaken to improve the selectivity of cAMPs, including sequence modification to optimize their physicochemical parameters (18,27,38,43).…”
mentioning
confidence: 99%